Establishing an Audio and Video Transport System for E-learning Based on Vinaren - Pham, Thai Bao; Tran, Anh Khoa; Dao, Van Tuyet (Journal of Technical Education Science, 2009)
Vietnam Research and Education Network (VinaREN) is a high speed backbone linking networks of major research and education organizations in Vietnam, and also linking regional, international research and education networks via TEIN2 with a bandwidth of 45/155 Mbps and via other international networks. With these advantages, VinaREN will be able to use perfectly in e-learning between organizations in Vietnam and also between Vietnam and other countries. To utilize the infrastructure of the high speed network, we propose a method using DVTS which is a transport audio and video system with very low delay. The DVTS system is well-known in many countries including Vietnam. This article goes deeply in establishing e-learning systems using DVTS based on VinaREN. The essential contents of the article include: 1. VinaREN structure. 2. Introducing DVTS. 3. Configurations and Testing. 4. Conclusion and development.